2018
DOI: 10.1007/s00027-018-0594-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbially-mediated indirect effects of silver nanoparticles on aquatic invertebrates

Abstract: Complex natural systems are affected by multiple anthropogenic stressors, and therefore indirect effects within food webs are increasingly investigated. In this context, dead organic matter (OM) or detritus provides a food source sustaining detrital food webs that recycle the retained energy through microbial decomposition and invertebrate consumption. In aquatic environments, poorly water-soluble contaminants, including nanoparticles (NPs), quickly adsorb onto OM potentially modifying OM-associated microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…phenolic content) also seems to negatively affect microbial resource niche breadth. The observed negative effects of sunlight on OM-associated microbial communities also likely reduce overall microbial respiratory activity and microbial biomass production, which itself may already retard microbiallymediated OM degradation (Tlili et al 2017) and growth of invertebrates that consume microbially-conditioned OM (Zhai et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phenolic content) also seems to negatively affect microbial resource niche breadth. The observed negative effects of sunlight on OM-associated microbial communities also likely reduce overall microbial respiratory activity and microbial biomass production, which itself may already retard microbiallymediated OM degradation (Tlili et al 2017) and growth of invertebrates that consume microbially-conditioned OM (Zhai et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it is known that sunlight can directly impair microbial communities through detrimental effects on DNA and extracellular enzymes (Santos et al 2013), or indirectly affect OM-associated microbial communities via photodegradation of OM into smaller palatable or harmful molecules depending on OM substrate (Mopper and Zhou 1990, Scully et al 1996, Obernosterer and Benner 2004, Hunting et al 2013a. This can be particularly relevant as besides their direct role in decomposing OM (Amado et al 2007), microbial communities also form an essential link towards invertebrates feeding on the OM by enhancing palatability and provisioning of nutrients (Graça et al 1993, Graça 2001, Danger and Robson 2004, Zhai et al 2018. Several invertebrates can detect resulting differences in food quality and select the most palatable food Graça 2008, Hunting et al 2013a), and adverse effects of sunlight on OM-associated biofilms have been observed to impair invertebrate growth (Franken et al 2005, Albarino et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Martínez-García et al (2009) [4] showed that in eukaryotes, the formazan production is only stopped after several hours, indicating a delayed toxic effect. The ETS vivo method as it has been applied up to this day as a rate measurement [4,17,18,19] presents several potential problems: INT is toxic because it interferes with the respiration chain in prokaryotes and eukaryotes, the kinetics of poisoning for prokaryotes and eukaryotes have very different time scales, but in mixed natural populations they occur simultaneously in the same sample, and apart from the respiratory chain other cell components might also reduce INT [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals have been the ECs more studied 42,45,59,61 , and less importance has been given to the effects of personal care products, plasticizers, perfluorinated compounds, pesticides, and other worrying ECs commonly found in water sources. Some works reported the effects of NPs in microbial behavior [62][63][64][65][66] , however, most of these studies did not focus on biofilms but on ecotoxicological tests using planktonic microorganisms [64][65][66] . Supplementary Table 2 summarizes some works that evaluated the effects of ECs on the microbiome of water systems, reporting the exposure conditions and the main effects observed.…”
Section: Microbial Ecotoxicology Of Ecsmentioning
confidence: 99%